THE EFFECT OF TOURIST ATTRACTIONS AND SERVICE QUALITY ON TOURIST SATISFACTION WITH DISCONFIRMATION AS A MEDIATION VARIABLE (Study on BUMDes Noyo Gimbal View Tourism) - Ika Nur Aprilliana; Lola Kurnia Pitaloka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of tourist attractions and service quality on tourist satisfaction through disconfirmation as a mediating variable at the BUMDes Noyo Gimbal View tourism destination. This research used a quantitative approach with a survey method by distributing questionnaires to tourists visiting the tourism destination. The data analysis technique used is path analysis with a stepwise regression approach and the Sobel test. The results of the study indicate that tourist attractions have a positive and significant effect on tourist satisfaction with a significant value of p < 0.001, and service quality also has a positive and significant effect on tourist satisfaction with a significant value of p < 0.001. In addition, tourist attractions influence tourist satisfaction through disconfirmation as a mediating variable with a significance value of p < 0.001, and service quality also influences tourist satisfaction through disconfirmation as a mediating variable with a significance value of p < 0.001. The findings of this study indicate that improving tourist attractions and service quality can increase tourist satisfaction through the tourism experiences perceived by visitors.